Reflective authenticity : rethinking the project of modernity - Ferrara, Alessandro, 1953- (Routledge, 1998)
"Has the Linguistic Turn sounded the death knell for the project of modernity? How can we appraise theoretical, practical and aesthetic claims in a universalist way without violating the premises of pluralism? Reflective Authenticity offers a challenging answer - an answer equally critical of the belief that the end of "grand narratives" implies the end of all kinds of universalism and of the intimation that conceiving of reason along communicative lines will by itself solve all the problems incurred by the project of modernity. Alessandro Ferrara suggests that the notion of reflective authenticity offers the key to a new kind of exemplary universalism which, differently from the generalizing universalism typical of modern thought, does not fall under the critique of foundationalism articulated by postmodernist thinkers."--Jacket